2018
DOI: 10.5152/ejbh.2018.3827
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Nutrition in Women with Benign Cyclic Mastalgia: A Case-Control Study

Abstract: The causes of mastalgia remain controversial. Our data supports some of the published studies, but not others. We propose that nutritional factors contribute less to the risk of mastalgia than is generally thought.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In a case-control study by İdiz et al it was found that patients with high BMI had significantly more mastalgia complaints than those with normal BMI (p<0.0001). 17 As per findings by Olfati et al, the patients with mastalgia had higher BMI (28.81±3.22). 18 The fact that BMI over 30 and weight gain in the last five years are determined as risk factors was crucial regarding its demonstration that weight management can be an approach in the prevention of mastalgia.…”
Section: Pathological Findingssupporting
confidence: 65%
“…In a case-control study by İdiz et al it was found that patients with high BMI had significantly more mastalgia complaints than those with normal BMI (p<0.0001). 17 As per findings by Olfati et al, the patients with mastalgia had higher BMI (28.81±3.22). 18 The fact that BMI over 30 and weight gain in the last five years are determined as risk factors was crucial regarding its demonstration that weight management can be an approach in the prevention of mastalgia.…”
Section: Pathological Findingssupporting
confidence: 65%
“…Johnson et al reported that mastalgia complaints were observed in women drinking alcohol twice as often 13 . In some previous studies, it was reported that drinking tea and smoking had no effect on mastalgia, but reducing caffeine intake would be beneficial for it 10 , 18 . Methyl-xanthine is found in products such as coffee, chocolate, black tea, and cola drinks, and there is a significant decrease in the sensitivity of breast tissue in more than 97% of women who completely avoid methyl-xanthine 19 .…”
Section: Discussionmentioning
confidence: 98%
“…However, in women who did not work, although the rate of mastalgia complaints was high, no significant results were found in regression analysis. One study reported that mastalgia complaints were higher among high school graduates 10 , while another study reported that mastalgia was more common in illiterate women or primary school graduates 18 . In our study, mastalgia was more common among primary school graduates.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, breast pain has also been reported to be associated with the use of certain medications, including estrogen and progesterone hormonal therapies, oral contraceptive pills, antihistamines, and antidepressants. Numerous other factors (24), such as depression (26), stress, anxiety, smoking, and nutrition (fatty diet, caffeine-based drinks), have been linked to the development of breast pain (27).…”
Section: U N C O R R E C T E Dmentioning
confidence: 99%